Characterization of 18th century Portuguese glass from Real Fábrica de Vidros de Coina. (August 2017) - Lopes, Filipa; Lima, Augusta; Pires de Matos, António; Custódio, Jorge; Cagno, Simone; Schalm, Olivier; Janssens, Koen
Abstract: This work reports the first systematic chemical characterization of Portuguese 18th century glassware. 28 selected glass fragments, recovered from an archaeological excavation carried out in the site where King D. João V of Portugal established an important glass manufacture, Real Fábrica de Vidros de Coina (Coina Royal Glass Factory), were studied. This factory operated from 1719 until 1747, the year in which the factory was transferred to Marinha Grande. The fragments were analysed by micro-energy dispersive X-ray fluorescence (micro-EDXRF), using a portable spectrometer ArtTAX, and scanning electron microscopy (SEM-EDX). The analytical data showed that a large variety of glass types was manufactured in that factory, namely soda-lime glass, mixed-alkali glass, high lime-low alkali glass, potash glass and lead glass. In general, the composition of the glass varies according to the function of the objects. It was demonstrated that micro-EDXRF can be an important tool to characterize museum glass objects when only in situ non-invasive analytical methods are allowed.